Exploring the Role of Indigenous Knowledge in Sustainable Agriculture in Kahungye Sub County Kabale District. - Ainebyoona, Emmanuel Jack (Kabale University, 2024)
This study examined the role of indigenous knowledge in sustainable agriculture in Kahungye sub-county, Kabale district, Uganda. The objectives were to explore farmers' perceptions of integrating indigenous knowledge with modern agricultural practices, assess the effectiveness of indigenous knowledge in tackling local agricultural challenges, and analyze socio-economic factors affecting its adoption. Using a descriptive research design, the study employed both quantitative and qualitative methods for data collection, including structured questionnaires for farmers and semi-structured interviews with key informants such as community leaders and the sub-county agricultural officer. The study population consisted of 120 individuals, including active farmers and community leaders in the Kahungye sub-county, with a sample size of 92 respondents determined using the Morgan and Krejcie table (1970). The findings indicated positive perceptions towards the integration of indigenous knowledge and its effectiveness in addressing agricultural challenges. Socio-economic factors, such as limited resource access and cultural beliefs, significantly influenced adoption. In conclusion, farmers showed a positive attitude towards merging indigenous knowledge with modern agricultural practices. Recommendations were made for targeted education campaigns, research support, and policy interventions to promote integration and enhance sustainability and rural livelihoods.